2020
DOI: 10.3389/fphys.2020.564387
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Vitamin D and Novel SARS-CoV-2 Respiratory Dysfunction – A Scoping Review of Current Evidence and Its Implication for COVID-19 Pandemic

Abstract: ObjectivesTo assess the association between vitamin D deficiency and increased morbidity/mortality with COVID-19 respiratory dysfunction.DesignScoping review.Data SourcesOvid MEDLINE (1946 to 24 of April 2020) and PubMed (2020 to 17 of September 2020).Eligibility Criteria for Selecting StudiesA search using the search terms: [(cholecalciferol or ergocalciferol or vitamin D2 or vitamin D3 or vitamin D or 25OHD) and (SARS-CoV-2 or coronavirus or COVID or betacoronavirus or MERS-CoV or SARS-CoV or respiratory inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 152 publications
1
32
0
Order By: Relevance
“…Interestingly, vitamin D deficiency has been found to be an independent risk factor for the development of ARDS, its severity, and mortality. Notably, a bulk of recent studies have reported that vitamin D deficiency is associated with severe COVID-19 and a higher risk for progression to ARDS [ 163 ]. Interestingly, the biologic pathways involved in the pleiotropic actions of vitamin D intersect with the dysregulated mechanisms during COVID-19-related ARDS, providing some possible explanations behind this association.…”
Section: How Could the Meta-inflammation In Obesity Intersect With Anmentioning
confidence: 99%
“…Interestingly, vitamin D deficiency has been found to be an independent risk factor for the development of ARDS, its severity, and mortality. Notably, a bulk of recent studies have reported that vitamin D deficiency is associated with severe COVID-19 and a higher risk for progression to ARDS [ 163 ]. Interestingly, the biologic pathways involved in the pleiotropic actions of vitamin D intersect with the dysregulated mechanisms during COVID-19-related ARDS, providing some possible explanations behind this association.…”
Section: How Could the Meta-inflammation In Obesity Intersect With Anmentioning
confidence: 99%
“…In the category of micronutrients, vitamin C [ 60 , 61 , 62 , 63 , 64 ] and the aforementioned vitamin D are included [ 48 , 56 , 65 , 66 , 67 , 68 ]. In an important recent review [ 69 ] the authors state that additional well-designed studies on the role of vitamin supplementations in order to prevent and/or treat COVID-19 infections should be mandatory. Indeed, considering the biological pathways, their dysregulation could be linked to COVID-19 outcomes: For these reasons, further investigation on vitamin C levels at the time of COVID-19 infection, during the infection, and after the infection is required to clarify their role as predictive biomarkers of disease severity.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, folate levels were demonstrated to be positively correlated with vitamin D levels in several studies [ 39 , 40 ]. To date, much has been published regarding a possible association between vitamin D deficiency, COVID-19 infection, and disease severity [ 20 , 21 , 22 , 23 , 24 , 41 ]. Moreover, Annweiler et al demonstrated that vitamin D supplementation was associated with a higher survival rate and lower COVID-19 disease severity [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression for PCFT is influenced, among other transcription factors, by vitamin D [ 1 , 19 ]. As vitamin D deficiency was associated with a higher infection rate and poor outcomes in COVID-19 patients [ 20 , 21 , 22 , 23 , 24 ], we hypothesized that folate levels in COVID-19 patients would be decreased.…”
Section: Introductionmentioning
confidence: 99%